THαβ Immunological Pathway as Protective Immune Response against Prion Diseases: An Insight for Prion Infection Therapy - Adam Tsou; Po-Jui Chen; Kuo-Wang Tsai; Wan-Chung Hu; Kuo-Cheng Lu (Viruses, 2022)
Prion diseases, including Creutzfeldt–Jakob disease, are mediated by transmissible proteinaceous pathogens. Pathological changes indicative of neuro-degeneration have been observed in the brains of affected patients. Simultaneously, microglial activation, along with the upregulation of pro-inflammatory cytokines, including IL-1 or TNF-α, have also been observed in brain tissue of these patients. Consequently, pro-inflammatory cytokines are thought to be involved in the pathogenesis of these diseases. Accelerated prion infections have been seen in interleukin-10 knockout mice, and type 1 interferons have been found to be protective against these diseases. Since interleukin-10 and type 1 interferons are key mediators of the antiviral THαβ immunological pathway, protective host immunity against prion diseases may be regulated via THαβ immunity. Currently no effective treatment strategies exist for prion disease; however, drugs that target the regulation of IL-10, IFN-alpha, or IFN-β, and consequently modulate the THαβ immunological pathway, may prove to be effective therapeutic options.